Malignant Transformation in a Mature Teratoma with Metastatic Deposits in the Omentum: A Case Report. (3rd October 2012) - Mandal, Shramana; Badhe, Bhawana A.
Abstract : Malignant transformation of a mature cystic teratoma (MCT) is a very rare complication with an incidence of 0.17–2%;. The most common form of malignant transformation of the MCT is squamous cell carcinoma. Other tumors arising in MCT include basal cell carcinoma, sebaceous tumor, malignant melanoma, adenocarcinoma, sarcoma, and neuroectodermal tumor. However malignant transformation with metastatic deposits in the omentum is extremely rare. The present case highlights the rarity of the occurrence of an omental deposits in a case of mature cystic teratoma with malignant transformation.